Foreword - Epure, Manuela (Journal of Economic Development, Environment and People, 2017)
Human capital is an important asset for any organization or country. Looking into the future, it seems that a human-centric vision of the work of time ahead that recognizes the people’s knowledge, talent, creativity and skills is the key positioning for a prosperous and inclusive economy. “Human capital means the knowledge and skills people possess that enable them to create value in the global economic system”. To measure the development of this capital is imperative to determine how it can be better used to achieve a solid economic growth. Similarly, at the company level, the development of the human capital means to secure a competitive advantage in the long run. More skilled and efficient employees will yield an increase of productivity and more competitive prices....